STUDENTS' PREFERENCES FOR DISASTER MEDICINE EDUCATION - Elena Valkanova; Rostislav Kostadinov; Rumyana Etova; Mariya Semerdjieva (Peytchinski Publishing, 2022)
Introduction: Disaster medicine training is in constant development. The effort to improve education could be facilitated by the students. They could actively participate in the process by providing useful feedback as well as preferences. Purpose: The aim of this study was to survey and analyze the students' preferences for disaster medicine education. Materials and methods: A cross-sectional survey was conducted among students of the Medical University of Plovdiv.166 students were surveyed ontheir attitude towards disaster medicine as well as preferences for the training course. Results: Disaster medicine training was considered a necessary part of the education. The most approved form of education was practical training, followed by elective course. The most desired topics are those regarding direct casualty management like first aid, first medical aid, triage and evacuation. Conclusions: To better respond to the expectations and educational needs of the students, modification of the training course could be considered.